Communication matters - Floyd, Kory (McGraw Hill LLC, 2022)
"An ideal textbook not only engages and excites students; it also provides relevant, contemporary, and high-quality support for instructors. Communication Matters, Fourth Edition, offers Connect, a flexible, groundbreaking, online learning platform that features LearnSmart, an adaptive diagnostic; hands-on learning activities; quizzes; and a fully integrated e-book. Connect enables instructors to better tailor class time to student needs and gives students more opportunities than ever for communication skills practice and assessment. I hope you will find this new edition of Communication Matters and its extensive instructional support to comprise a well-integrated package of engaging and contemporary materials for the introductory course"--Provided by publisher.